Low-Carbon Development Strategies for Power Generation Expansion in Sub-Saharan Africa: Insights from an Optimisation-Based Analysis for Kenya - Xavier S. Musonye; Brynhildur Davíðsdóttir; Ragnar Kristjánsson; Eyjólfur I. Ásgeirsson; Hlynur Stefánsson (Energies, 2025)
Energy production and consumption are major contributors to global anthropogenic greenhouse gas emissions. Sub-Saharan African countries face the challenge of harnessing diverse energy sources to meet rising demand affordably while curbing emissions. This study uses the optimisation-based Kenya-TIMES model to explore low-carbon strategies for Kenya’s power generation from 2020 to 2050. A business-as-usual (BAU) scenario is compared with four low-carbon scenarios: carbon tax, renewable portfolio standard, renewable energy subsidies, and a hybrid of subsidies and carbon tax. The analysis reveals that geothermal, wind, and hydropower dominate the energy mix until 2035 across all scenarios. After 2035, coal capacity in the BAU scenario is replaced by solar, gas, and biomass in low-carbon scenarios. While all low-carbon strategies, except the renewable energy subsidy scenario, meet Kenya’s nationally determined contribution (NDC) emission reduction targets by 2050, the hybrid scenario emerges as the most effective and cost-efficient pathway. Although achieving significant emissions reductions, the carbon tax and renewable portfolio standard scenarios result in higher system costs. The results indicate that an integrated optimisation-based approach can identify optimal energy development pathways that leverage local resources to accommodate growth and enhance energy access while minimising costs and emissions.